PRINCIPLES OF LENINIST PARTISANSHIP IN LITERATURE AND ART - Choriyev Sanjar Hamzaevich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The partisanship of Soviet literature and art, the Marxist-Leninist doctrine and party leadership of literature and art, and the manifestation of partisanship in Uzbek Soviet literature and art are discussed